Using data analytics to understand visitors online search interests: the case of Douro Museum - Carvalho, Aida (2020)
Regional museums are relatively recent museum structures that emerged in the late 19th century after universal exhibitions. They are museums specifically dedicated to the representation of a given population in a specific territorial context, highlighting the fundamental traits that characterize the nature and essence of that community, differentiating it from others. In northern Portugal, law no. 125/97, created the Douro Museum, a territory museum that represents the natural and cultural heritage of the demarcated Douro region, the first demarcated and regulated region of the world, in 1756, by Marques de Pombal, extending over an area of of 250,000 hectares, between Barqueiros and Barca d'Alva along the Douro River and its tributaries. The museum has a “polynuclear structure distributed throughout the Douro region, based in Peso da Régua” (art. 2), serving as an element for mobilizing tourists, mainly through its main temporary exhibitions, videos, etc. In an information society, characterized by the empowerment of citizens with regard to their ability to independently obtain information and, in the process, to leave their footprint, it is crucial to understand and anticipate their interests. In this way, the supply and responsiveness of tourism agents and regional actors will be increased, making them better able to decide for an offer better suited to the real interests of visitors and even enable to influence them. This article aims to know the profile of tourists / consumers through their online behavior, trying to understand what kind of information they are looking for, which keywords are most used and searched using the fundamentals of Data Analytics and using the Google Trends tool. Moreover, this study enables to better understand the connection between online search interests and the reality of the Douro Museum visitants. This approach is nowadays a major contribute to bridge the gap between visitors needs/interests and tourism player’s strategies definition, making Data Analytics a fundamental tool to enable decision support systems.